2008
DOI: 10.1089/jwh.2006.0295
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Cervical HPV and Cytological Abnormalities in Association with Reproductive Factors of Rural Nigerian Women

Abstract: The prevalence of cervical HPV and SIL in Okene, Nigeria, is consistent with reports from other African regions. Improved access to healthcare and cervical cancer screening programs may help to decrease transmission of HPV and subsequent cervical cancer in underprivileged areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 27 publications
9
22
0
Order By: Relevance
“…This is similar to a study done by Schartz et al in Okene central Nigeria which found a prevalence of 19.7% [6]. The prevalence of HR-HPV in the study done in Ibadan by Thomas et al was 16.6%.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to a study done by Schartz et al in Okene central Nigeria which found a prevalence of 19.7% [6]. The prevalence of HR-HPV in the study done in Ibadan by Thomas et al was 16.6%.…”
Section: Discussionsupporting
confidence: 90%
“…The low-risk HPV were found in 6.6% and mixed infections of more than one HPV type occurred in 33.5% of HPV-positive cases. A similar incidence of 21.6% was found in Okene, north-central Nigeria with the high-risk HPV prevalence of 16.6 and 3.5% having mixed infections [19].…”
Section: Burden Of Hpv Infection and Regional Variation Of Genotypessupporting
confidence: 70%
“…Besides, there was no statistically significant difference in the mean age of women diagnosed with HPV in a study conducted in a rural area at Okene North central Nigeria [20] . Akarolo-Anthony and colleagues observed in their study in an urban area in Abuja a significant inverse linear association between age and the prevalence of HPV infections.…”
Section: Hpv and Age In Nigeriamentioning
confidence: 80%
“…However, no general public [15][16][17][18][19][20] . It is worthy of note that even in the report of the Information Centre on HPV and Cancer held August 22 nd , 2014, data on Human Papillomavirus [5] was generalized based on national prevalence figure gotten from studies done at Ile-Ife, Ibadan and Okenne respectively [17, 18 & 20] .…”
Section: Particularly High Prevalence Is Seen Inmentioning
confidence: 99%
See 1 more Smart Citation